A Multi-Disciplinary Review on the Aerobiology of COVID-19 in Dental Settings - Dabiri, Darya; Conti, Samuel Richard; Sadoughi Pour, Niloufar; Chong, Andrew; Dadjoo, Shaahin; Dabiri, Donya; Wiese, Carol; Badal, Joyce; Hoogland, Margaret Arleen; Conti, Heather Raquel; Taylor, Travis Roger; Choueiri, George; et al. (Frontiers in Dental Medicine, 2021)
The COVID-19 pandemic pushed dental health officials around the world to reassess and adjust their existing healthcare practices. As studies on controlled COVID-19 transmission remain challenging, this review focuses on particles that can carry the virus and relevant approaches to mitigate the risk of pathogen transmission in dental offices. This review gives an overview of particles generated in clinical settings and how size influences their distribution, concentration, and generation route. A wide array of pertinent particle characterization and counting methods are reviewed, along with their working range, reliability, and limitations. This is followed by a focus on the effectiveness of personal protective equipment (PPE) and face shields in protecting patients and dentists from aerosols. Direct studies on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are still limited, but the literature supports the use of masks as an important and effective non-pharmaceutical preventive measure that could reduce the risk of contracting a respiratory infection by up to 20%. In addition to discussing about PPE used by most dental care professionals, this review describes other ways by which dental offices can protect patients and dental office personnel, which includes modification of the existing room design, dental equipment, and heating, ventilation, and air conditioning (HVAC) system. More affordable modifications include positioning a high-efficiency particulate air (HEPA) unit within proximity of the patient's chair or using ultraviolet germicidal irradiation in conjunction with ventilation. Additionally, portable fans could be used to direct airflow in one direction, first through the staff working areas and then through the patient treatment areas, which could decrease the number of airborne particles in dental offices. This review concludes that there is a need for greater awareness amongst dental practitioners about the relationship between particle dynamics and clinical dentistry, and additional research is needed to fill the broad gaps of knowledge in this field.